2019
DOI: 10.1158/1535-7163.mct-18-0577
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Dose and Schedule Effects of AZD2811 Nanoparticles Targeting Aurora B Kinase for Treatment of Diffuse Large B-cell Lymphoma

Abstract: Barasertib (AZD1152), a pro-drug of the highly potent and selective Aurora B kinase inhibitor AZD2811, showed promising clinical activity in relapsed/refractory diffuse large B-cell lymphoma (DLBCL) patients administered as a 4-day infusion. To improve potential therapeutic benefit of Aurora B kinase inhibition, a nanoparticle formulation of AZD2811 has been developed to address limitations of repeated intravenous infusion. One of the challenges with the use of nanoparticles for chronic treatment of tumors is … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…The function of Aurora C kinase is not well established, but studies suggested it has similar function to Aurora B kinase ( Sasai et al, 2004 ; Yan et al, 2005 ). There are several Aurora kinase inhibitors that have progressed to clinical development, including tozasertib ( Zhang et al, 2020 ), barasertib ( Floc’h et al, 2019 ) and MK-5108 ( Amin et al, 2016 ). Previous studies showed that GSK-1070916 has a broad antitumor effect on cancer cell lines and in tumor xenograft models including lung, breast, colorectal, and leukemia ( Hardwicke et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…The function of Aurora C kinase is not well established, but studies suggested it has similar function to Aurora B kinase ( Sasai et al, 2004 ; Yan et al, 2005 ). There are several Aurora kinase inhibitors that have progressed to clinical development, including tozasertib ( Zhang et al, 2020 ), barasertib ( Floc’h et al, 2019 ) and MK-5108 ( Amin et al, 2016 ). Previous studies showed that GSK-1070916 has a broad antitumor effect on cancer cell lines and in tumor xenograft models including lung, breast, colorectal, and leukemia ( Hardwicke et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, during the Preprints (www.preprints.org) | NOT PEER-REVIEWED | Posted: 17 November 2021 G2 phase, phospho-H3 co-localizes with the Aurora B kinase which is known to be frequently overrepresented in NHL patients [216,217]. Interestingly, both preclinical [218] and clinical [219] data have supported the potential for the Aurora kinase inhibition as a new therapy for DLBCL patients.…”
Section: Targeting Other Posttranslational Modifications Of Histonesmentioning
confidence: 99%
“…In this context, encapsulation of this type of PROTACs could undoubtedly improve efficacy and reduce toxicity. Novel formulations of this type of chemical entities have shown potential, and some of them like small molecules aurore kinase inhibitors are currently in clinical development (Floc'h et al, 2019). Another limitation of PROTACs is the ubiquitous expression of some of the POI in non-transformed tissues.…”
Section: Advantages and Disadvantages Of Protacs Technologymentioning
confidence: 99%